Developing Islamic Religious Education in Public Universities: A Multisite Study of Curriculum and Learning Systems in Indonesia - Ahmad Buchori Muslim; Luluk Elyana; Supean Chemo (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2026)
This study examines the development model of Islamic Religious Education (PAI) in public universities, focusing on curriculum development and learning systems at Universitas Brawijaya and Universitas Negeri Malang. Using a qualitative multi-site design, data were collected through observation, interviews, and document analysis, then examined through individual case and cross-site analyses. The findings reveal a centralised-decentralised development pattern. Centrally, curricula are structured around institutional vision and mission, competencies, syllabi or Semester Lesson Plans, and teaching materials aligned with national regulations. Decentrally, lecturers adapt content, strategies, media, enrichment activities, and assessment to disciplinary contexts. Both institutions implement competency-based, learner-centred, thematic curricula informed by a social reconstruction approach. Their learning systems promote active, contextual, and inquiry-based learning, supported by tutorials at Universitas Brawijaya and Tafaqquh fii Dinil Islam at Universitas Negeri Malang. Nevertheless, religion-science integration is more apparent in teaching practice than in formal curriculum documents, and affective or character assessment lacks a comprehensive standard framework. This study maps PAI development in public universities and calls for stronger curriculum integration, lecturer pedagogical competence, enrichment activities, and authentic, measurable character assessment.